Redesign of water-diesel emulsion fuel mixer - Mahadi, Abram Anggit; Santoso, Budi; Ubaidillah, Ubaidillah; Lenggana, Bhre Wangsa (Applied Research and Smart Technology (ARSTech), 2022)
Emissions and fuel consumption are essential parameters to indicate the working of a combustion engine. This paper discusses the methods to achieve lower emissions and efficient fuel consumption. One of the methods is by making emulsion fuel. The emulsion-making methods are surfactant emulsion, micro-emulsion, ultrasonic emulsion, and real-time emulsion non-surfactant (RTES). In the research, the emulsion fuel is a mixture of B30 Biodiesel and water without surfactant that is supplied in real-time after being mixed in a mixer. The ratio is 85% biodiesel and 15% water. The RTES mixer in the old model has a big size, and high-power consumption of about 150-433,5 W. This research's purpose is to develop a simple design and low power consumption of the RTES Mixer. The new RTES mixer design only needs 150 W motor power. Its dimension is more superficial and produces tiny droplets with a main diameter range between 0.1 to 0.5 ?m, with good-mixed visually.